Application of Blood Flow Restriction to Optimize Exercise Countermeasures for Human Space Flight - Behringer, Michael; Willberg, Christina (Frontiers in Physiology, 2019)
In recent years there has been a strong increase in publications on blood flow restriction (BFR) training. In particular, the fact that this type of training requires only low resistance to induce muscle strength and mass gains, makes BFR training interesting for athletes and scientists alike. For the same reason this type of training is particularly interesting for astronauts working out in space. Lower resistance during training would have the advantage of reducing the risk of strain-induced injuries. Furthermore, strength training with lower resistances would have implications for the equipment required for training under microgravity conditions, as significantly lower resistances have to be provided by the training machines. Even though we are only about to understand the effects of blood flow restriction on exercise types other than low-intensity strength training, the available data indicate that BFR of leg muscles is also able to improve the training effects of walking or running at slow speeds. The underlying mechanisms of BFR-induced functional and structural adaptations are still unclear. An essential aspect seems to be the premature fatigue of Type-I muscle fibers, which requires premature recruitment of Type-II muscle fibers to maintain a given force output. Other theories assume that cell swelling, anabolic hormones, myokines and reactive oxygen species are involved in the mediation of BFR training-related effects. This review article is intended to summarize the main advantages and disadvantages, but also the potential risks of such training for astronauts